Comparison of risk assessment models of BRCA1 and BRCA2 mutation carrier in patients with breast cancer - Rybchenko L.A.; Bychkova A.M.; Skyban G.V.; Klymenko S.V. (Medičnì Perspektivi)
Analysis of efficiency of the algorithm BOADICEA using and Manchester scoring system to predict the carrier of BRCA1 and BRCA2 mutations in Ukranian patients with breast cancer was performed. Materials for this study were the results of clinical, imunogistological, pathogistological, genealogical, molecular genetic researches of 146 patients with breast cancer. Calculations of mutations risk were performed using BOADICEA algorithm and Manchester scoring system. In the total group of patients the area under the curve while predicting BRCA1 mutations with algorithm BOADICEA was 0.86, with Manchester scoring system - 0.84, and in calculation of the combined risk of BRCA mutations - 0.83 and 0.84, respectively. However, statistical difference between the areas of algorithms has not been established (p> 0.05), it indicates to the same discriminatory power of the test models. Better sensitivity, specificity, positive and negative predictive value of results of BOADICEA algorithm was reached in 6% of BRCA1 probability and in 8% threshold of BRCA1/2 mutations. The Manchester scoring system has showed the best operating characteristics with 6 and 13-point probability of BRCA1 and BRCA1/2 mutations respectively. Patients with probability of mutations with such thresholds may be offered molecular study of pathogenic alleles.